IMPLEMENTATION OF COOPERATIF LEARNING MODEL TYPE THINK PAIR SHARE (TPS) TO IMPROVE ARABIC VOCABULARY MASTERY OF STUDENTS SDN 3 BEUREUNUEN - Nyak Mustakim; Riska Riska (Pedir Research Institut, 2021)
This study aims to improve the Arabic vocabulary mastery of fourth grade students at SDN 3 Beureunuen by using a Think Pair Share cooperative learning model approach. This study uses a classroom action research design. Research data obtained through observational data collection, tests and documentation. The research subjects were all fourth grade students of SDN 3 Beureunuen which consisted of 20 students consisting of 13 female students and 7 male students. Tehkink Data analysis used by researchers is to reduce data, present data and draw conclusions. The results showed that the application of the Think Pair Share type of cooperative learning model can improve the Arabic vocabulary mastery of fourth grade students at SDN 3 Beureunuen, this is evident from the acquisition of the average score of students in the first cycle of 64.5 and experienced a significant increase in the second cycle of 91.25